Positive body image and young women's health: Implications for sun protection, cancer screening, weight loss and alcohol consumption behaviours. (January 2016) - Andrew, Rachel; Tiggemann, Marika; Clark, Levina
This study examined the link between positive body image and a range of health behaviours. Participants were 256 women who completed an online questionnaire measuring body appreciation, body dissatisfaction, sun protection, cancer screening, seeking medical attention, weight-loss behaviour and alcohol and tobacco consumption. Results indicated that body appreciation was positively related to sun protection, skin screening and seeking medical attention and negatively related to weight-loss behaviour. Body appreciation explained unique variance, over and above body dissatisfaction, in sun protection, skin screening and weight-loss behaviour. These results have implications for interventions to improve adherence to health behaviours.